A feminine deconstruction of the concept and tenets of Arole in Oyo empire and its place in Yoruba philosophy (2020)
The concept of Arole occupied and still has a significant position in Oyo Empire. Arole among the Yoruba is the first male child in a family. Such child has sociological, economic and religious advantages over his siblings. In fact, a family without an Arole. regardless of the number of female children, is somewhat incomplete. Thus, a wife goes all out to ensure she “produces” one for her family in Order to make her motherhood complete and her place as a wife secured. This paper seeks to deconstruct this concept embedded in the beliefs of the Yoruba by offering a rational reflection on the tenets of Arole and the significant power it wields among children, in the Oyo Empire, the family and the Yoruba society at large. This is done from a feminine perspective in order to analyze, critically, Arole from a mother's or sister's viewpoint. This study seeks to answer the following questions: what is Arole to a Yoruba and the intent of identifying a child as one? What are the advantages and disadvantages (if any) of being an Arole? What are the tenets of Arole? Is Arole still relevant in a Contemporary Yoruba society? These questions are answered in this study with a view to offering a female holistic view of Arole, presenting the logical flaws in the concept, and unraveling the tenets of Arole and its place among the Yoruba in the 21" Century. Recommendations were also suggested.